Anda di halaman 1dari 10

Solved Examples based on Progression

Example 1:

Find the sum of the series

1 – 3 + 5 – 7 + 9 – 11 + …… upto n terms.

Solution :

This problem can be solved by different approachesm of course some one is tricky,
some one is little bit lengthy. Now you have to judge which one is suitable for
your.

Method I:

In the problem, it is not mentioned that n is even or n is odd. So, take the
different case.

Case I:

When n is even

i.e. n = 2m

Now, given series can be broken into two series like

(1 + 5 + 9 + 13 +…m terms)

= m/2 [2 + (m – 1)4] – m/2 [2 × 3 + (m – 1)4]

= m/2 (–4) = –2m

= –n

Case II:

When n is odd

i.e. n = 2m + 1.

[1 + 5 + 9 +…(m + 1) terms] – [3 + 7 + 11 +… m terms]

= m+1/2 [2 + 4m] – m/2 [6 + (m–1)4]

= m/2 [2 + 4m – 6 – 4m + 4] + 1 + 2m

Trans Web Educational Services Pvt. Ltd


B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
= 2m + 1

=n

Method 2:

1 – 3 + 5 – 7 + 9 ……… upto n terms

Case I:

When n is even i.e. n = 2m

Take two terms of given series at a time then above series becomes
(–2) + (–2) + (–2) +…… upto m times.

So, sum of series = –2m

= –n

Case II:

When n is odd i.e. n = 2m + 1

1 + (2 + 2 + 2 +…… upto m times)

=1+2m

= n.

Method 3:

1 – 3 + 5 – 7 + 9 – 11 +… upton terms

This series is also written as

1 + 3.(–1) + 5.(–1)2 + 7.(–1)3 + 9.(–1)4 +…… upto n terms

1 + [3.(–1) + 5.(–1)2 + 7.(–1)3 + 9.(–1)4 +…… upto (n–1) terms]

And seeing clearly, it is arithmetic geometric series is and common difference is 2


and the first term of geometric series is (–3) and common ratio is (–1).

Sn = 1 + [3.(–1) + 5.(–1)2 + 7.(–1)3 +…+ (2n–1).(–2)n–1]

Let Sn–1 = 3.(–1) + 5.(–1)2 +…+ (2n–1).(–1)n–1

Trans Web Educational Services Pvt. Ltd


B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
–Sn–1 = 3.(–1)2 +…+ (2n–3) (–1)n–1 + (2n–1)(–1)n

Subtracting, we get,

2 Sn–1 = 3–2 [(–1) + (–1)2 +…+ (–1)n–2] –(2n–1)(–2)n

Case I:

When n is even

2 Sn–1 = –3 –2n+1 = –2 (n+1)

Sn–1 = –(n+1)

Sn = 1 + Sn–1 = –n

Example 2:

The sum of three consecutive terms in A.P. is 27 and the sum of their squares is
293, then find all three terms.

Solution:

If we take three terms of an A.P. like a, a + d. and a + 2d

then a + (a + d) + (a + 2d) = 3(a + d) = 27 and

a2 + (a+d)2 + (a+2d)2 = 293

In this way calculation is very long, so we take the terms like

α – ß, α, α, α + ß are the required numbers.

so (a – ß) + α + (α + ßb) = 27

or 3α = 27

⇒α=9

Now (α–ß)2 + α2 + (α+ß)2 = 293.

or α2 + ß2– 2αß + α2 + α2 + ß2 + aαß = 293

or 3α2 + 2ß= 293

or 2ß2 = 293 – 3α2 = 293 – 3(92) = 293 – 243 = 50.

or ß2 = 25

Trans Web Educational Services Pvt. Ltd


B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
ß = +5

So the numbers are 4, 9, 14. Negative values will just reverse the order. (Ans.)

Example 3:

Find the common difference of an A.P. whose first term is 100 and the sum of
whose first six terms is five times the sum of the next six terms.

Solution:

Let the common difference is d.

∴ Sn = n/2 [2a + (n–1)d]

Sn = 6/2 [2 × 100(n–1)d] (i)

= 3[200 + 5d]

S7.12 = 7thterm+12thterm/2 × 6(using equation 4)

= 100+6d+100+11d/2 × 6

= (200 + 17d) 3 (ii)

According to problem 5 × eq. (i) = eq. (ii)

So 5 × (200 + 7d)3 = 3(200 + 5d)

Or 1000 + 85d = 200 + 5d

Or 80 d = –800

So d = –10

Example 4:

The sum of three consecutive numbers in G.P. is 39 and their product is 729
then find all three numbers.

Solution :

Let α/ß, α, αß are required numbers


Product = α3 = 729 = 93
∴α=9
α/ß + α + αß = 39 (given)
Trans Web Educational Services Pvt. Ltd
B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
α(1/ß + 1 + ß) = 39

Multiplying each term by ß


9(1 + ß + ß2) = 39ß
Or 9ß2 + 9ß + 9 – 39ß = 0
Or 9ß2 – 30ß + 9 = 0
ß = 30+√900–324/18 = 30+√576/18
ß = 30+24/18 = 54/18, 6/18 = 3, 1/3
So numbers are 3, 9, 27 or 27, 9, 3. (Ans.)

Example 5:

If Sp denote the sum of the series 1 + rp + r2p +…… ∝ and sp denote


the sum of series 1 – rp + r2p …… (assume |r| < 1) then prove that

Solution:

Sp = 1 + rp + r2p +…… (i)


p
=1/1–r
sp =1/1–rp
(here common ratio is – rp)
∴ Sp + sp = 1/1–rp + 1/1–rp = 1+rp+1–rr/1–(rp)2
= 2/1–r2p
= 2 S2p

Example 6:

Prove that 0.423232323…… is a rational number

Solution:

This problem could be solved by either using progression or


without progression.
Let S = 0.4232232………

Method 1:

S = 4/10 + 23/1000 + 23/100000 +...


= 4/10 + 23/103 + 23/105 +...
= 4/10 + 23/103 [1 + 1/102 + 1/104 +...]
Trans Web Educational Services Pvt. Ltd
B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
= 4/10 + 23/103 [1/1–1/102]
= 4/10 + 23/103 × 100/99
= 4/10 + 23/103 = 419/990
So S is a rational number. (Proved)

Method 2:

1000 S = 423.232323 ……
10 S = 4.232323 ……..
Subtracting, we get,
990 S = 419
S = 419/990

So S is a rational number. (Proved)

Example:

If a2, b2, c2 are in A.P. show that b+ c, c, c+ a, a + b are in H.P.

Solution:

a2, b2, c2 are in A.P.

So adding ab + bc + ca to each term

a2 + ab + bc + ca, b2 + ab + bc + ca. c2 + ab + bc + ca will also be in A.P.

i.e. a(a + b) + c(b+a), b(a+b) + c(b+a), c(c+b) + a(b+c) are in A.P.

i.e. (a+c)(a+b), (b+c)(a+b),(c+a(b+c) are in A.P.

dividing each term by (a+b)(b+c)(c+a)

1/b+a, 1/c+a, 1/a+b are in A.P.

So b + c, c+a, a+b are in H.P. (Proved)

Example :

If the AM between ‘a’ and ‘b’ is twice as greater as the GM, show that a/b =
7+4√3

Trans Web Educational Services Pvt. Ltd


B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
Solution:

A.M. =a/b

G.M. =√ab

We have given

AM = 2 GM

a+b/2 = 2√ab

a+b–4 (ab)1/2 = 0

divide each term by ‘b’

(a/b) + 1 – 4 (a/b)1/2 = 0

or (√a/b)2 – 4 √a/b + 1 = 0

∴ √a/b = 4+√16–4/2 = 4+2√3/2 = 2+

Squaring both sides, we get,

a/b = (2+√3)2 = 4 + 3 + 4√3 = 7+4√3

Example :

The sequence N of natural numbers is divided into classes as follows

2 3 4

5 6 7 8 9

10 11 12 13 14 15 16

----------------------------------------------

--------------------------------------------------

Find the sum of the numbers of j-th row

Solution:

Numbers of element in j-th row = (2j–1)

So number of elements in first j rows


Trans Web Educational Services Pvt. Ltd
B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
= Σ(2j-1) = 2Σ j–Σ 1

= 2 ×j(j+1)/2 – j

= j(j+1–1)=j2

So number of elements in first (j-1) class = (j-1)2

So first element of j-th class = (j–1)1 +1

So sum of (2j-1) terms of A.P. with first term, (j-1)2

Common difference, 1

1 = (2j–1)/2 [2{(j–1)2 + 1}+(2j–1).1]

= (2j – 1) (j2 – 2j + 2 + j – 1)

= (2j – 1) (j2 – j + 1). (Ans.)

Example :

If a1, a2, ……, an are in arithmetic progression, where ai > 0 for all I, show
that

1/√a1 + √a2, 1/√a2 + √a3, ......., 1/√an–1 + √an = n–1/√a1 + √an

Solution:

L.H.S. = 1/√a1 + √a2, 1/√a2 + √a3, ......., 1/√an–1 + √an = n–1/√a1 + √an

= (√a1+√a2)/(√a1+√a2)(√a1–√a2), (√a2+√a3)/(√a2+√3)(√a2–√a3) +…+


(√an–1–√an)/(√an–1+√an)(√an–1–√an)

= √a1 – √a2/a1 – a2 + √a2 – √a3/a2 + a3 +...+ √an–1 + √an/an–1 + an

Since a1, a2, a3, ……, an are in A.P.

So a2 – a1 = a3 – a2 = …… = an – an–1 = d (say)

Adding all terms, we have an – a1 = (n–1)d (i)

So L.H.S. = √a1–√a2/–d + √a2–√a3/d +...+ √an–1–√an/d

=–[√a1–√a2 + √a2–√a3 +...+ √an–1–√an]

= √an+√a1/d = √an–√a1/(an–a1)/(n–1) = (n–1)(√an–


√a1)/(√an+√a1)(√an–√a1) (from I)

Trans Web Educational Services Pvt. Ltd


B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
= n–1/√an+√a1 = R.H.S. (Proved)

Example :

If S be the sum, P the product and R the sum of the reciprocals of n terms of a
G.P.

Solution:

Given S = a + ar + ar2 +……+ arn–1

P = a.ar.ar2 …… arn–1

R =1/a + 1/ar + 1/ar2 +...+ 1/arn–1

So, S =a(1–r)r/1–r

P = an.rn(n–1)/2

R =(1/a)(1–1/rn)/1–1/r

So L.H.S. = (S/R)r = [a(1–rr)/(1–r)×1/a(1–1/rn)/(1–1/r)]

= [a2(1–rn)(r–1/r)/(1–r)(rn–1/rr)]n

= [a2(1–rn)(r–1)rn/r(1–r)(1–rn)]n = [a2rn–1]n = [anrn(n–1)/2]2

= P2 = R.H.S. (Proved)

Example:

Find the sum to n terms of the series


1.3.5 + 3.5.7 + 5.7.9. +……

Solution:

Here tn = (2n–1)(2n+1)(2n+3)
∴ Sn = tn = Σ(2n–1)(2n+1)(2n+3)
= Σ((2n)2 –12) (2n+3)
= Σ(4n2 –1)(2n+3)
= Σ(8n3 + 12 n2 – 2n – 3)
= 8 n2(n+1)2/4 + 12 n(n+1)(2n+1)/6 – 2 n(n+1)/2 – 3n
= n[2n (n+1)2 + 2(n+1)(2n+1)–(n+1) –3]
= n[2n (n2 + 2n + 1) +2(2n2 + 3n + 1) – n – 4]
= n[2n3 + 4n2 + 2n2 + 4n2 + 6n + 2 – n – 4]
Trans Web Educational Services Pvt. Ltd
B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204
= n[2n3 + 8n2 + 7n – 2]
Hence Sn = n[2n3 + 8n2 + 7n – 2]

Example:

Find the sum of n terms of the series


1/1.2.3.4 + 1/2.3.4.5 + 1/3.4.5.6 +.........

Solution:

tr = 1/r(r+1)(r+2)(r+3)
tr+1 = 1/(r+1)(r+2)(r+3)(r+4)
tr/tr+1 = r+4/r
r tr = (r + 4) tr+1
r tr = (r + 1) tr+1 + 3 tr+1
Putting r = 1, 2, ……, n–1
adding we get, t1 – ntn = 3 [t2 + t2 + t3 +…+ tn]
or 4t1 – ntn = 3[t1 + t2 +…+ tn] = 3 Sn
Sn = 1/3 [4t1 – ntn]
=1/3 [1/1.2.3 – m/3(n+1)(n+2)(n+3)]
= 1/18 – 1/3(n+1)(n+2)(n+3) (Ans.)

Example:

Sum of the following series to n terms:


1/1.3 + 2/1.3.5 + 3/1.3.5.7 + 4/1.3.5.7.9 +......

Solution:

tm = m/1.3.5.7 ...... (2m+1)


= 1/2 [2m+1–1/1.3.5.7 ...... (2m+1)]
=1/2 {1/1.3.5 ...... (2m–1) – 1/1.3.5 ...... (2m+1)}
m = 1: t1 =1/2 {1 – 1.3}
m = 2: t2 =1/2 {1/1.3 – 1/1.3.5}
m = 3: t1 =1/2 {1/1.3.5 – 1/1.3.5.7}
m = n: tn =1/2 {1/1.3.5..... (2n–1) – 1/1.3.5......(2n+1)}
Adding,

Sn = t1 + t2 +………tn = 1/2 {1 – 1/1.3.5 ..... (2n+1)}

Trans Web Educational Services Pvt. Ltd


B – 147,1st Floor, Sec-6, NOIDA, UP-201301
Website:www.askiitians.com Email. info@askiitians.com
Tel:0120-4616500 Ext - 204